ANALISIS NILAI TAMBAH SERABUT KELAPA SEBAGAI BAHAN BAKU PEMBUATAN ANEKA PRODUK (KASUS PT. SUMBER UTAMA LESARI KECAMATAN TANANTOVEA KABUPATEN DONGGALA) - Opiyanti Opiyanti; M.R Yantu; Sisfahyuni Sisfahyuni (Universitas Tadulako, 2013)
The aim of the research was to identify characteristics of PT Sumber Utama Lestari business, to analyze added value of coconut fiber as raw material for assorted product produced by PT Sumber Utama Lestari, and to analyze the sensitivity of the PT Sumber Utama Lestari revenue generated from the activities of fiber coconut processing to produce assorted products. The research location was pusposely he determined. Respondents purposively chosen were leaders and workers of the PT Sumber Utama Lestari who were directly involved in the coconut fiber processing. Data collected in this research were primary and secondary. Tool used to analyze the data were descriptive-qualitative analysis, value added analysis, sensitivity analysis, and income analysis. The PT Sumber Utama Lestari had 38 fulltime workers, 12 part time workers. The average production month-1 was 168,000 kg of coconut fiber. The value added gained was IDR 1,928 kg-1 of coconut fiber raw material used. Increasing the coconut fiber product price 5% would result in raising the income of PT Sumber Utama Lestari as much as IDR 312,921,669 but 5% decrease in the product price would reduce the income as much as IDR 267,561,669. The income of the PT Sumber Utama Lestari was IDR 290,241,669 month -1. Key Words : Assorted products, coconut fiber, and value added analysis.